Inovasi Mewujudkan Tujuan Pendidikan Nasional Bagi Peserta Didik pada Pembelajaran IPAS di SDN 9 Tanjung Gadang Kecamatan Tanjung Gadang Kabupaten Sijunjung - Weni Yulastri; Ratnawilis; Siska Lanora; Syatria Hasni; Yustina; Rinda Riska; Fitria Nilda (STKIP Subang, 2025)
This article aims to describe innovative approaches in Natural and Social Sciences (IPAS) learning to achieve the goals of national education, particularly in fostering piety and noble character among elementary school students at SD Negeri 9 Tanjung Gadang, Sijunjung Regency. This study employed a descriptive qualitative approach with a reflective practice design based on the elementary school context. Data were collected through classroom observations, teachers’ reflective pedagogical practices, and documentation studies, and were analyzed using a descriptive-thematic technique. The findings reveal that innovation in IPAS learning can be implemented through the integration of Qur’anic verses related to natural phenomena, gratitude-based learning approaches, the habituation of scientific ethics, the use of Muslim scientists’ biographies as moral exemplars, and the application of science-and-character-based assessment. These innovations enable IPAS learning to function not only as a medium for scientific knowledge acquisition but also as a means of internalizing spiritual values and developing students’ moral character. Therefore, innovative and contextual IPAS learning contributes significantly to the holistic achievement of national education goals at the elementary education level.